The Limits of Command and Control - Young, David (2021)
This thesis examines the role of the human operator in command and control systems designed and developed for the US Air Force during the 1950s and 1960s. As understood within the discourse of defence research, command and control involved the efficient capture and management of information from the battlefield in the pursuit of a particular military strategy. The digital computer, although then still very much the highly protean object of military-industrial-university research networks, was repeatedly proposed as a crucial technology that would allow for greater and more accurate control of the battlefield.